DOES A REDUCTION IN TAX RATES INFLUENCE TAX AGGRESSIVENESS? AN ANALYSIS WITH ADDITIONAL FACTORS - Wahyuni, Fitri Ilma; Andriani, Sri (Riset: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2024)
This study investigates the effect of reduction tax rates in Indonesia and other factors that may impact tax aggressiveness. This study employs multiple linear regression analysis, using E-Views 12 as analytical software. A sample of fourteen real estate and property companies listed on the Indonesia Stock Exchange (IDX) for 2017 to 2023 was identified through purposive sampling. This study relies on secondary data derived from the company's financial statements. The results showed that the reduction in tax rates and the presence of independent commissioners did not significantly affect tax aggressiveness. In contrast, institutional ownership and profitability factors positively correlate with tax aggressiveness, while leverage shows a negative correlation. It is expected that the results of this study will contribute to the development of taxation policies for companies in Indonesia, aiming to reduce aggressive taxation practices and assist companies in their tax-related decision-making framework.